The Implementation of War on Drugs Program in One of the Municipalities of Ifugao Province - Guay, Moises A; Cawi, Robinson D (Bina Nusantara University, 2021)
The research aimed to explore the implementation of the war on drugs program in the municipality of Alfonso Lista, Ifugao. The research utilized descriptive qualitative research design to determine the interrelated factors affecting the implementation of the war on drugs program, setbacks encountered by the implementers thereof, the mechanism employed to counter the challenges in its implementation, and the suggestions for efficient implementation. Thematic analysis was used to determine the themes derived from the interview. The barangay chairmen, community members, church and educational officers, Philippine National Police (PNP) personnel, and Local Government Units (LGU) officials served as the key informants through purposive sampling technique. In addition, the researchers wanted to venture on the binding foundation program or a localized war on drugs program, which would significantly predict support for the anti-crime and anti-drug campaign as encountered by the police officers, LGU officials, and the community in the municipality of Alfonso Lista, Ifugao. Given all these, the result of the research relatives to the factors and setbacks encountered by the police officers, LGU officials, and community, including the mechanisms employed among them to counter the challenges in the implementation of the war on drugs program, will be the basis in crafting a localized war on drugs program.